Case Report: Constrictive Pericarditis in a Patient With Isolated Anomalous Right Upper Pulmonary Venous Return - Bou Chaaya, Rody G.; Herrmann, Jeremy L.; Rao, Roopa Akkadka; Fisch, Mark D.; Ephrem, Georges (Frontiers in Cardiovascular Medicine, 2020)
Thirty-eight-year-old male presented for evaluation of abdominal swelling, lower extremity edema and dyspnea on exertion. Extensive work-up in search of the culprit etiology revealed the presence of an Anomalous Right Upper Pulmonary Venous Return (ARUPVR) into the Superior Vena Cava (SVC). During the attempted repair, the pericardium was found to be thickened and constrictive. Only one other case of co-existent partial anomalous pulmonary venous return and constrictive pericarditis (CP) has been reported. The patient underwent a warden procedure with pericardial stripping with good outcomes at 45 days post-operatively. Thus, the presence of severe heart failure symptoms in the setting of ARUPVR should prompt further investigations. Also, further cases are needed to help guide management in these patients.